STUDIES ON THE EFFECTS OF TEMPERATURE ON THE SURVIVAL OF CERCARIA - OKHRIYAL, B.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The survival period of the three different cercariae i.e. liver fluke amphistome and schistosome at 4, 10, 15, 20,25, 30, 35 and 40°C reveal a sequential decrease in the survival period with regard to increase in tmperature. Taking into consideration the results of the present study and a comparison with the views of earlier wokers it appears that the temperature of water influences the life span of cercariae directly. The humidity has also been found to influence the metabolism of cercariae directly but to some extent.